1982
DOI: 10.1152/ajpregu.1982.242.1.r3
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of the human circadian system with two interacting oscillators

Abstract: Human subjects during extended isolation from environmental time cues show complex variations in timing and duration of sleep with a progressive pattern, which eventually results in rest-activity and body temperature rhythms having different average periods. We present a model where temperature and rest-activity are each governed by an oscillator of the van der Pol type, denoted x and y, respectively. The oscillators affect one another through "velocity" type coupling, the effect of x on y being about four tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
143
2

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(153 citation statements)
references
References 0 publications
8
143
2
Order By: Relevance
“…Because the present study never determined whether the observed rhythms at T were indeed endogenous-capable of continuing, even when activity, meals, light, and so on were homogenized at all phases of T-we do not know whether the process underlying them can truly be referred to as a biological oscillator. Previous models of the circadian system did indeed regard human sleep/wake processes as having a separate circadian oscillator (Wever et al, 1975;Kronauer et al, 1982). These models posited two mutually interactive oscillators (or groups of oscillators) to underlie the human circadian system.…”
Section: Discussionmentioning
confidence: 99%
“…Because the present study never determined whether the observed rhythms at T were indeed endogenous-capable of continuing, even when activity, meals, light, and so on were homogenized at all phases of T-we do not know whether the process underlying them can truly be referred to as a biological oscillator. Previous models of the circadian system did indeed regard human sleep/wake processes as having a separate circadian oscillator (Wever et al, 1975;Kronauer et al, 1982). These models posited two mutually interactive oscillators (or groups of oscillators) to underlie the human circadian system.…”
Section: Discussionmentioning
confidence: 99%
“…The polysomnograms (EEG, EMG, EOG, ECG and respiration) were monitored to score sleep stages by the manual of Rechtschaffen and Kales. 4 We measured sleep latency to N R E M sleep stages 1 (Sl) and 2 (S2) according to the guidelines5 of the multiple sleep latency test (MSLT) twice a day on two consecutive days during the morning (O5):3O-l1:30 h) and the afternoon (13:30-14:30 h). For CE odor exposure, we used a small electrically operated apparatus with a built-in plastic bottle for emitting the odor in the bedroom and placed it under the footboard of the bed.…”
Section: Methodsmentioning
confidence: 99%
“…Circadian rhythms for muscarinic receptors have been described in autopsy material from human cortex (Perry et al 1977) and from rat brain (Kafka et al 1981). Moreover, Kronauer et al (1982) propose the existence of a' strong oscillator', termed the' X oscillator', which regulates the circadian organization of REM sleep, temperature, and cortisol. Since cholinergic agonists lower body temperature and stimulate cortisol secretion, one wonders whether acetylcholine acts upon or through the 'X oscillator'.…”
Section: Chronobiologymentioning
confidence: 99%